STRATEGI GURU FIKIH DALA M MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DI MTs MIR’ATUL MUJAHID KAMPUNG BAJO - Muhammad Aksal; Askari Zakaria; Hartono (Universitas Sains Islam Al Mawaddah Warrahmah Kolaka, 2025)
The fiqh teacher's strategy is a method used by teachers in improving student learning outcomes, especially at MTs Mir'atul Mujahid Kampung Bajo. The learning strategy here provides very significant results on student learning outcomes. The formulation of the problem is as follows: (1) What are the principles of the preparation of the fiqh teacher's strategic plan in improving the learning outcomes of students at MTs. Mir'atul Mujahid Kampung Bajo?, (2) How is the implementation of the fiqh teacher's strategy in improving the learning outcomes of students at MTs. Mir'atul Mujahid Kampung Bajo?, (3) What are the results of the implementation of the fiqh teacher's strategy on improving the learning outcomes of students at MTs. Mir'atul Mujahid Kampung Bajo?. This research uses a qualitative approach carried out at MTs Mir'atul Mujahid Kampung Bajo. The data collection techniques used are observation, interviews, and documentation and the source of the data are fiqh teachers and students at MTs Mir'atul Mujahid Kampung Bajo. The principles of preparing a learning strategy plan include three things that need to be considered, namely being oriented to learning objectives, considering the comparison of materials and time density, and considering classroom management methods by taking into account the number of students. Then there are three types of learning strategies used to improve student learning outcomes at MTs Mir'atul Mujahid Kmapung Bajo, namely expository learning strategies, Contextual Teaching and Learning learning strategies, and cooperative learning strategies. The implementation of the strategy is known to run significantly, so this shows that the learning process using the learning strategy runs effectively. It is also said that what supports the effectiveness of learning that occurs is the provision of motivation in the form of advice to students at the end of learning, the fiqh teacher believes that in addition to the application of learning strategies to improve learning outcomes, other opportunities that can be combined are by always giving advice to students, because this is based on fiqh subjects that are closely related to the practice of amaliyah in a student's life.